5PSQ-105 Effect of data reporting system in outpatient pharmacy of tumour specialist hospital. (2nd March 2018) - Yang, G; Wang, Z; Zhou, H; He, F; Huang, P
Abstract : Background: Reporting and analysis of unreasonable dispensing data of an outpatient pharmacy and blocking unreasonable prescriptions of doctors play an active role in reducing irrational prescriptions and ensuring the safety of patients' medication. The use of information technology will greatly improve the reporting rate of such data and the effectiveness of the analysis of the problem. At present, the application of related systems or procedures in China, especially in tumour specialist hospitals, is still to be strengthened. Purpose: To improve the efficiency and accuracy of drug dispensing in an outpatient pharmacy, so as to ensure the safety and rational use of drugs. Material and methods: Pharmacists have developed the His data reporting system as a supervisory tool, which is used to real-time report and record the problems occurring during the dispensing process, including dispensing errors, blocking the doctor's irrational medication, special drug problems, drug withdrawal and so on. In this study, the data of outpatient pharmacy dispensing during the operation of the system from 10 August 2016 to 10 March 2017 were collected, and the data were segmented and collated. Results: The analysed results of this data showed that the accuracy rate of prescribing prescriptions was as high as 99.63%, the unqualified prescription rate was 0.37%, of which the doctor's unreasonable prescriptions accounted for the most, up to 88.84%: the following problem is the internal errors in dispensing, which accounted for 8.37%. Of the irrational prescriptions made by doctors, indications and clinical diagnosis not matching the wrong prescription accounted for 73.91%, other reasons include unreasonable dosage, excessive total amount of drugs and so on. In addition, 12 prescriptions for special drugs were irrational, accounting for 2.58% of irrational prescriptions, 80% of which were classified as codeine and emergency anaesthetic prescriptions exceeding the specified time of use. Conclusion: Since the outpatient pharmacy started the application of the His data reporting system, it not only provides more security for the patients, but also strengthens the relationship between pharmacists and clinicians, to better reflect the role and value of pharmacists. No conflict of interest